Intramural jejunal leiomyoma as a cause of colic. (8th November 2019) - Miles, S.; Davis, W.; Craft, W. F.
Summary: A 15‐year‐old Thoroughbred gelding showjumper presented with colic after a history of chronic mild, intermittent colic. He was refractory to medical management. At surgery, he was found to have a 15‐cm intramural mass in the distal jejunum, approximately 3 m orad to the ileum. Histopathology post‐operatively revealed a leiomyoma. Leiomyomas in horses are rare. They have been reported most commonly in the reproductive tract, with other rare reports in the oesophagus and omentum. To the knowledge of the authors, there are no reports of identification and treatment of non‐strangulating obstruction of the jejunum caused by a leiomyoma. The horse recovered from his surgery and went on to compete at the same level of showjumping as previous to the surgery with no further episodes of colic. Based on this report, leiomyoma should be a differential for small intestinal obstruction in the future.